Dynamic metabolomic and transcriptomic profiling reveals yellow flower development in Camellia perpetua, a rare continuously flowering golden Camellia species - Xianliang Zhu; Haidu Jiang; Xinfeng Pan; Jiaxin Fu; Lihui Peng; Jin Zhang; Jianmin Tang; Rong Zou; Bo Zhao; Xiao Wei; Shengfeng Chai (Horticulture Advances, 2024)
Abstract The golden camellia, a highly valued ornamental plant, belongs to the Chrysantha section, the sole group in the Camellia genus that produces yellow flowers. The cultivation and broader application of this unique species have been significantly hindered by the scarcity of golden camellia and the limited knowledge of the molecular mechanisms governing yellow flower development. To investigate the dynamics of metabolite accumulation and gene expression during the yellow flower formation of C. perpetua, a continuously flowering golden camellia, a comprehensive metabolomic and transcriptomic analysis was performed across five distinct developmental stages. This analysis identified 1,160 metabolites, with flavonoids constituting the largest proportion at 21.6%. Comparative transcriptomic profiling indicated that differentially expressed genes (DEGs) associated with photosynthesis were predominantly active during the early stages of flower development, while DEGs involved in the flavonoid biosynthesis pathway showed a marked increase as the flowers matured. The integrated metabolomic and transcriptomic data highlighted the pivotal regulatory role of the flavonoid biosynthesis pathway in the formation of yellow flowers in C. perpetua, identifying 50 key genes and 17 crucial metabolites and mapping their interaction networks. Furthermore, weighted gene co-expression network analysis pinpointed several hub genes, such as flavonol synthase, which are likely critical to flavonoid production due to their elevated expression levels, particularly in the early bud and yellowing phases. This study provides valuable insights into the molecular pathways that underlie yellow flower development in golden camellia species.